2018
DOI: 10.1016/j.gca.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Thallium (Tl) sorption onto illite and smectite: Implications for Tl mobility in the environment

Abstract: Clay minerals play a relevant role in the transport and fate of trace elements in the environment. Though illite has been referred as an important Thallium (Tl) bearing phase in soils, mechanisms and affinity of thallium for clay minerals remain poorly known. This study investigated the sorption behavior of thallium as Tl(I) onto illite and smectite, two clay minerals occurring mainly in soils and sediments. Different sorption experiments were carried out under various pH conditions and Tl concentrations, in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 64 publications
7
20
0
Order By: Relevance
“…HREE, MREE and related elements that migrated into the coal seam in a dissolved form could be mostly adsorbed by clay minerals, which has been reported by previous studies and confirmed by relevant experimental studies [78,86,[109][110][111][112][113][114]. Experimental studies have shown that the sorption of REE and related elements mainly depended on adsorption sites of clay minerals, namely, hydroxyl units on Al-O hexahedron or Si-O tetrahedron sheets [115][116][117]. An increase in the three types of hydroxyl groups supplied more edge and basal adsorption sites for trace elements in sample 3, which resulted in the accumulation of HREE, MREE and related elements in zone I.…”
Section: Accumulationsupporting
confidence: 61%
“…HREE, MREE and related elements that migrated into the coal seam in a dissolved form could be mostly adsorbed by clay minerals, which has been reported by previous studies and confirmed by relevant experimental studies [78,86,[109][110][111][112][113][114]. Experimental studies have shown that the sorption of REE and related elements mainly depended on adsorption sites of clay minerals, namely, hydroxyl units on Al-O hexahedron or Si-O tetrahedron sheets [115][116][117]. An increase in the three types of hydroxyl groups supplied more edge and basal adsorption sites for trace elements in sample 3, which resulted in the accumulation of HREE, MREE and related elements in zone I.…”
Section: Accumulationsupporting
confidence: 61%
“…Therefore, it is unlikely that Tl 2 S would precipitate directly from these waters. Alternatively, Tl could also be dominantly sorbed onto the surface of clay minerals in these non‐euxinic reducing sediments, especially Na‐illite (e.g., Martin, Wissocq, Benedetti, & Latrille, ; Voegelin et al, ). Given that Tl isotope fractionation appears to be muted during sorption that is not associated with Tl oxidation (Nielsen et al, ), it would not be expected that clay minerals are fractionated relative to the water column.…”
Section: Discussionmentioning
confidence: 99%
“…The sorption data was successfully modelled with 1-pK Diffuse layer model [73]. In another study, thallium is found to associate with illite in natural environment and sorption studies reveal that TI(I) sorbs more onto illite than smectite [74]. The affinity for TI follows this sequence: MnO 2 > illite > smectite = ferrihydrite > = Al 2 O 3 = goethite > SiO 2 .…”
Section: Illitementioning
confidence: 95%
“…The affinity for TI follows this sequence: MnO 2 > illite > smectite = ferrihydrite > = Al 2 O 3 = goethite > SiO 2 . However, in presence of Rb, Cs, Ti adsorption to illite is less [74].…”
Section: Illitementioning
confidence: 95%